-2(5w-4)+4w=6+4(2w-2)

Simple and best practice solution for -2(5w-4)+4w=6+4(2w-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5w-4)+4w=6+4(2w-2) equation:



-2(5w-4)+4w=6+4(2w-2)
We move all terms to the left:
-2(5w-4)+4w-(6+4(2w-2))=0
We add all the numbers together, and all the variables
4w-2(5w-4)-(6+4(2w-2))=0
We multiply parentheses
4w-10w-(6+4(2w-2))+8=0
We calculate terms in parentheses: -(6+4(2w-2)), so:
6+4(2w-2)
determiningTheFunctionDomain 4(2w-2)+6
We multiply parentheses
8w-8+6
We add all the numbers together, and all the variables
8w-2
Back to the equation:
-(8w-2)
We add all the numbers together, and all the variables
-6w-(8w-2)+8=0
We get rid of parentheses
-6w-8w+2+8=0
We add all the numbers together, and all the variables
-14w+10=0
We move all terms containing w to the left, all other terms to the right
-14w=-10
w=-10/-14
w=5/7

See similar equations:

| 2(3-6a)=30 | | 145=10x-8x145=10x-8x | | -13-7n=-6-9(n+) | | b^2+9b+9=0 | | 19+3m=3 | | 7+35b=710b | | 4v-4+4(2v+1)=-3(v+1) | | 8+15b=310b | | 2x+6+3=5+3x+7 | | 6k-15-9k=-57 | | -4(-5)=d | | .50(x-3)=2.5 | | -5(2+x)=10 | | 2(5x+1)=7 | | -4(w+1)=-3(5w-4)+5w | | 12. 4(z+6)=40 | | 5(7+x)=-75 | | -14=3u+7 | | -83=7x+16-16x | | 2x+4(-6x-12)=-4 | | 2-2y=22-3y | | 6(y-4)-6=-5(-5y+4)-5y | | 1x-39=3/4x | | -2(x-6)=16 | | t=12÷3 | | 6+a=0 | | -7+3=f | | 35x+80=915 | | -3(4w-1)+6w=1+2(5w-4) | | 1/5x+x=180 | | s=4+2 | | 2h÷7=19 |

Equations solver categories